An Integrated “Multi-Omics” Comparison of Embryo and Endosperm Tissue-Specific Features and Their Impact on Rice Seed Quality - Galland, Marc; He, Dongli; Lounifi, Imen; Arc, Erwann; Clément, Gilles; Balzergue, Sandrine; Huguet, Stéphanie; Cueff, Gwendal; Godin, Béatrice; Collet, Boris; Granier, Fabienne; Morin, Halima; et al. (Frontiers in Plant Science, 2017)
Although rice is a key crop species, few studies have addressed both rice seed physiological and nutritional quality, especially at the tissue level. In this study, an exhaustive “multi-omics” dataset on the mature rice seed was obtained by combining transcriptomics, label-free shotgun proteomics and metabolomics from embryo and endosperm, independently. These high-throughput analyses provide a new insight on the tissue-specificity related to rice seed quality. Foremost, we pinpointed that extensive post-transcriptional regulations occur at the end of rice seed development such that the embryo proteome becomes much more diversified than the endosperm proteome. Secondly, we observed that survival in the dry state in each seed compartment depends on contrasted metabolic and enzymatic apparatus in the embryo and the endosperm, respectively. Thirdly, it was remarkable to identify two different sets of starch biosynthesis enzymes as well as seed storage proteins (glutelins) in both embryo and endosperm consistently with the supernumerary embryo hypothesis origin of the endosperm. The presence of a putative new glutelin with a possible embryonic favoured abundance is described here for the first time. Finally, we quantified the rate of mRNA translation into proteins. Consistently, the embryonic panel of protein translation initiation factors is much more diverse than that of the endosperm. This work emphasizes the value of tissue-specificity-centered “multi-omics” study in the seed to highlight new features even from well-characterized pathways. It paves the way for future studies of critical genetic determinants of rice seed physiological and nutritional quality.